O Infant Motor Profile (IMP) : tradução e propriedades psicométricas - Machado, Luiza Ribeiro (Universidade Federal de São Carlos, 2022)
Introduction: The Infant Motor Profile (IMP) is an instrument for quantitative and qualitative assessment of the gross and fine neuromotor development of infants aged between three and 18 months, or until they acquire independent and mature walking (three months after the gait acquisition). The IMP is quintessential to the scientific and clinical scope, as it considers the Neuronal Group Selection Theory; it is designed according to the biopsychosocial model when evaluating the structures and functions of the infant's body and activities; possesses good psychometric properties; additionally of being a quick and easy application instrument. General aims:To elaborate a scoping review protocol that aims to verify the psychometric properties of the original version of the Infant Motor Profile; in addition to translating it from British English to Brazilian Portuguese. Conclusion: Through manuscript 1 - Psychometric properties of the Infant Motor Profile (IMP): a scope review protocol (accepted for publication in PLOS ONE) was possible to identify several materials published in databases and the gray literature. Therefore, it will be possible to systematically summarize the most relevant information about the IMP and disseminate the knowledge provided by it. While manuscript 2 - Infant Motor Profile (IMP): translation and concurrent validity for Brazilian infants (submitted to JAMA Pediatrics) was prepared with the aim of enabling the IMP access for Brazilian health professionals. The process of successfully translating the IMP into Brazilian Portuguese showed the maintenance of its concurrent validity with the Alberta Infant Motor Scale. In this way, the use of IMP by Brazilian health professionals in childcare becomes viable, optimizing early detection, design, and monitoring of the effectiveness of early physical therapy intervention programs.
Infant Motor Profile (IMP): translation and psychometric properties
Keywords: Lactente; Desenvolvimento infantil; Infant Motor Profile; Propriedades psicométricas; Tradução; Infant; Child Development; Psychometric properties; Translation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL